2021
DOI: 10.3390/jdb9040048
|View full text |Cite
|
Sign up to set email alerts
|

Self-Control of Inflammation during Tail Regeneration of Lizards

Abstract: Lizards can spontaneously regenerate their lost tail without evoking excessive inflammation at the damaged site. In contrast, tissue/organ injury of its mammalian counterparts results in wound healing with a formation of a fibrotic scar due to uncontrolled activation of inflammatory responses. Unveiling the mechanism of self-limited inflammation occurring in the regeneration of a lizard tail will provide clues for a therapeutic alternative to tissue injury. The present review provides an overview of aspects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 79 publications
2
6
0
Order By: Relevance
“…These findings, coupled with previous research, suggest that a persistent and likely polarized immune response toward M2 healing inflammation promotes regrowth and may protect new tissues by maintaining self‐recognition or survival 64,65 (He et al. 2022).…”
Section: Resultssupporting
confidence: 62%
“…These findings, coupled with previous research, suggest that a persistent and likely polarized immune response toward M2 healing inflammation promotes regrowth and may protect new tissues by maintaining self‐recognition or survival 64,65 (He et al. 2022).…”
Section: Resultssupporting
confidence: 62%
“…Heterophils, a type of granulocyte equivalent to mammalian neutrophils, are recruited to the wound site to participate in the phagocytosis of tissue debris and defense of various microbes in reptiles. Immunostaining revealed that these heterophils inhibit rather than trigger inflammation (7). In this case, we noted pyogranulomatous inflammation consisting of heterophils and macrophages phagocytizing rod-shaped bacteria, suggesting a chronic stage of bacterial infection.…”
Section: Discussionmentioning
confidence: 63%
“…Aside the mechanical role of hyaluronate in promoting cell movement and organization for the formation of new tissues in the regenerating tail, this large glycosaminoglycan has also a strong immunesuppressive activity, like in tumours (Aya & Stern, 2014;Petrey & de la Motte, 2014). Various factors contribute to the creation of immune-evasive condition that allow tail regeneration such as production of antimicrobial peptides, serpins and presence of arginase positive M2-like healing macrophages and of T-cell regulatives (Tregs) among blastema cells (Alibardi, 2020(Alibardi, , 2021bHe et al, 2021). The recruitment of macrophages, likely of type M2 (healing), has been also shown during spinal cord and tail regeneration in gecko lizards (Londono et al, 2020;Wang et al, 2019).…”
Section: Immunosuppressed Like Tumoursmentioning
confidence: 99%
“…Other studies suggest that the production of HMGB1 (High Motility Group protein B1) in cells of the amputated tail of lizards represses the activity of Toll receptors (TLR2/4) in cells present at the injury sites that usually activate inflammation (He et al, 2021). Another anti‐inflammatory protein activated in the regenerating tail of geckos is VAV1 (vav guanine nucleotide exchange factor 1) that inhibits the migration of macrophages in injured tissues.…”
Section: The Blastema Is Immunosuppressed Like Tumoursmentioning
confidence: 99%
See 1 more Smart Citation